Mental health care delivery and quality of service provision in Brazil - Lauro Estivalete Marchionatti; Kátia Bones Rocha; Natalia Becker; Natan Pereira Gosmann; Giovanni A. Salum (Elsevier, 2023)
Public mental health system in Brazil is structured through "The Psychosocial Care Network (Rede de Atenção Psicossocial, RAPS)''. This coordinated system comprises primary care, specialized mental health care, crisis management services, inpatient units, deinstitutionalization initiatives, and psychosocial rehabilitation programs. In this narrative review, we aim to provide an overview of mental health care delivery in Brazil by assessing three aspects of the RAPS: structure, operationalization, and current state. For reviewing its structure, we start by overviewing the public health system, then examining the psychiatric reform, as well as the law and policy that established the components of the community-based mental health system in the country. Regarding the operationalization, we review recommendations for how the different components of the system should be coordinated, as well as directions for practices at the assistance level. Finally, we review the results of the mental health system, including official data and academic publications assessing coverage, funding, and quality of care. Drawing on the results from this review, we highlight fragilities that indicate three future directions for strengthening the mental health provision in Brazil: establishing appropriate mechanisms for systematic assessment of the mental health system, improving the recommendations regarding the coordination and integration of services, and promoting evidence-based practices across the different levels of care provision.